TAKBIRAN MASYARAKAT DESA KEBUNDURIAN KABUPATEN KAMPAR PADA MALAM IDUL FITRI - Amanan Amanan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Many ways are done by humanity to manifest gratitude to Allah SWT with the coming of the holy month of Ramadan, as well as the compilation of the end of the holy month of Ramadan which is celebrated on the 1st day of the year. Riau Province as a center of Malay language and culture (UU. Hamidy, 1988: 51) has many traditions. In order to welcome the holy month of Ramadan and also end a very lucky month there. Ramadhan and Eid al-Fitr, for example in the Kampar Kanan area (Kuok, Tiro Air Tiris, Rumbio, Bangkinang, etc.) in welcoming the holy month of Ramadhan there are visitors to the bath